Anthropocene - Anthropocene (Elsevier, 2026)
Anthropocene is an interdisciplinary peer-reviewed journal answering questions about the nature, scale and extent of interactions between people and Earth processes and systems. The scope of the journal includes the significance of human activities in altering Earth's landscapes, oceans, the atmosphere, cryosphere, and ecosystems over a range of time and space scales - from global phenomena over geologic eras to single isolated events - including the linkages, couplings, and feedbacks among physical, chemical, biological, and social dimensions of Earth systems. The journal also addresses how such alterations can have profound effects on, and implications for, human society. As the scale and pace of human interactions with Earth systems have intensified in recent decades, understanding human-induced alterations in the past and present is critical to our ability to anticipate, mitigate, and adapt to changes in the future. The journal aims to provide a venue to focus research findings and debates toward advancing predictive understanding of sustainable human interactions with Earth systems-one of the grand challenges of our time.
FI 0.86
Q2
Keywords: Earth; Space & Environmental Sciences; Sustainable Development; Acuerdos transformativos; Transformative agreements; Antropoceno; Sistemas terrestres; Sostenibilidad